Pengembangan Kapasitas Usaha Klasterisasi Bawang Merah “Diversifikasi Produk Bawang Merah dan Strategi Pemasaran Di Era Digitalisasi” - Zaenul Arif; Nugroho Adhi Santoso; Bangkit Indarmawan Nugroho; Aang Alim Murtopo; Sarif Surorejo; Syefudin Syefudin; Bayu Aji Santoso (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of shallot cluster business capacity is crucial in increasing the competitiveness and welfare of farmers, especially in the digital era. This community service aims to explore the potential for shallot product diversification and formulate effective marketing strategies through the use of digital platforms. Through a qualitative approach with case studies on selected shallot clusters, this study identified various processed shallot products that have added value, such as fried shallots with various flavors, shallot floss, shallot paste, and other derivative products. The analysis of digital marketing strategies includes the use of social media, e-commerce, and other online platforms to expand market reach and increase interaction with consumers. The results of community service are expected to provide practical recommendations for the development of shallot cluster business capacity, encourage product innovation, and optimize the use of digital technology in marketing strategies to achieve sustainable economic growth for farmers.